A case of two spellings for Humboldt’s blue-winged mosquito (Diptera: Culicidae) - Harbach, Ralph E.; Evenhuis, Neal L. (Zootaxa, 2021)
While adding taxon names to the Systema Dipterorum database (Evenhuis & Pape 2021), one of us (NLE) discovered that Humboldt (1819) had spelled the proposed name of a nominal mosquito species in two ways. He described the species, which was found in swampy places along the Magdalena River near Tenerife, Colombia, as Culex cyanopennis on page 340 and afterwards referred to it as Culex cyanopterus on pages 345 and 349. Both names have the same meaning: cyano- (Gr. kyanos, dark blue), pennis (L. penna, feather, wing) and pteron (Gr. feather, wing). The species was named for the perceived color of the wings: “Alæ cæruleæ, splendore semi-metallico…” (wings blue, a bright semi-metallic). On page 345, Humboldt states, translated from the French: “We have been informed in the Rio de la Magdalena that in Simitì no other Culex than the jejen [je·jén: Sp., gnat, mosquito] was known in the past. You can spend the night there quietly, because the jejen is not a nocturnal insect. Since the year 1801, the big blue-winged mosquito (Culex cyanopterus) has shown itself in such abundance that the poor inhabitants of Simitì do not know how to get a peaceful sleep.” Thus, in addition to having the same meaning, the two names are associated with the same locality.